Transmedia Storytelling and the New Era of Media Convergence in Higher Education - Kalogeras, Stavroula; SpringerLink (Online service). (London : Palgrave Macmillan UK, 2014)
In the age of media convergence, stories have morphed into new forms yet their core purpose remains the same, which is to pass on knowledge and information. This book argues that the inherent interactivity of the internet and the emotional engagement of story can lead to innovative pedagogies in media-rich environments.
Keywords: Science